Women's Nutrition: Folate/Folic Acid - Caroline Dunn; Gail Kauwell (EDIS)
To decrease a baby’s chances of having certain types of births defects, mothers need to have already been consuming enough of the vitamin called folate, or folic acid, before they become pregnant. This article provides information about the folate/folic acid needs of women who are capable of becoming pregnant, including its role in preventing birth defects, sources, and strategies for meeting the recommended intake. This 4-page fact sheet was written by Caroline Dunn and Gail Kauwell, and published by the UF Department of Food Science and Human Nutrition, February 2015. (Photo Credit: Mike Watson Images/moodboard/Thinkstock.com)